The Effect of Tax Incentives, Modernization of Tax Administration and Tax Sanctions on MSME Tax Payer Compliance (Case Study at KPP Pratama Badung Utara) - N K Errika Sindy Septiani; N Sentosa Hardika; A A Putri Suardani (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Tax revenue have an important role for Indonesian’s development. The ratio of taxpayer compliance and tax revenue in Indonesia has increased, but in some areas the ratio of taxpayer compliance, especially for MSME has decreased as at KPP Pratama Badung Utara. In an effort to maintain taxpayer compliance, mainly due to the Covid-19 pandemic, the government has implemented several policies by providing tax incentives, modernizing the tax administration system and imposing tax senctions on businesses that are direcly affected, especially for MSME.The purpose of this study are to examine the effect of tax incentives, modernization of the tax admin-istration system and tax sanctions on msme taxpayer compliance. For the type of data are used primary data that obtained through from distribution of questionnaires and secondary data from documentation. The sample of this research is based on purposive sampling method with total sample 99 MSME taxpayers registed at the KPP Pratama Badung Utara. Statistical testing is using Partial Least Square (PLS) with SmartPLS 3.3.9. The study finds that (a)tax incentives have a positive and significant effect on MSME taxpay-er compliance,(b) modernization of tax administration systemhave a positive and significant effect on MSME taxpayer compliance, (c) tax sanctions have a positive and significant effect on MSME taxpayer compliance.